RESEARCH ON ACCELERATED FATIGUE TESTING METHOD OF THE WORM AND GEAR TRANSMISSION - BAI GuoZhen; WANG QiaoRan (Jixie qiangdu)
Based on the fatigue life damage theory,the load contribution to the fatigue life was analyzed,then dispensed part frequency of small load to other load levels. The corresponding stress distribution was obtained using the software of ANSYS;the fatigue damage of worm gear was calculated by correlating results of ANSYS and the time history using the software of n Code,and compared with the experimental results. This paper presented specific calculation method,and analyzed reliability and feasibility of accelerated fatigue of worm and gear.